1995
DOI: 10.1136/jmg.32.6.458
|View full text |Cite
|
Sign up to set email alerts
|

The dental phenotype in familial adenomatous polyposis: diagnostic application of a weighted scoring system for changes on dental panoramic radiographs.

Abstract: A weighted scoring system (Dental Panoramic Radiograph Score) taking into consideration the nature, extent, and site of osseous and dental changes on dental panoramic radiographs in familial adenomatous polyposis is described. The weighting takes into consideration the incidence of the anomaly in the general population. The reliability of the system was tested by application to 85 people known to be affected by clinical or mutation analysis, 30 people lacking mutation in the adenomatous polyposis gene, and 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 25 publications
3
38
0
Order By: Relevance
“…They are present in 46% to 93% of FAP patients, an incidence 4 to 20 times higher than in control groups (3% to 16%). (38)(39)(40) In keeping with previous studies, (2) osteomas were located predominantly in the upper and/or lower mandible in our patients, and their presence was positively correlated with the presence of teeth anomalies. (41,42) Patients with scintigraphic evidence of osteoma(s) were, on average, younger than those without osteomas, albeit nonstatistically significantly.…”
Section: Discussionsupporting
confidence: 91%
“…They are present in 46% to 93% of FAP patients, an incidence 4 to 20 times higher than in control groups (3% to 16%). (38)(39)(40) In keeping with previous studies, (2) osteomas were located predominantly in the upper and/or lower mandible in our patients, and their presence was positively correlated with the presence of teeth anomalies. (41,42) Patients with scintigraphic evidence of osteoma(s) were, on average, younger than those without osteomas, albeit nonstatistically significantly.…”
Section: Discussionsupporting
confidence: 91%
“…A recent meta-analysis showed that the frequency of osseous jaw and dental anomalies in affected individuals were 65.35% and 30.48%, respectively [14]. There has been growing interest in characterizing these alterations because they may precede CRC and may be used as an early disease diagnostic marker [15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Osteomas in the oral and maxillofacial region are typical of Gardner syndrome and have been found in more than 50% of patients with FAP [78] (Fig. 5).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…These benign tumours commonly develop in the paranasal sinuses, the mandible and maxilla. There is a less frequent but significant association with odontomas and supernumerary teeth [78]. Focal increases in bone density within the gnathic bones are also described [78].…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation